CONDITIONS OF FORMATION OF INFORMATION YOUTH CULTURES - N.V. Volkova (Academy of Cognitive and Natural Sciences, 2004)
The article deals with the problem of students' information culture forming, the ways of raising a level of information culture of Ukrainian youth.